Implementation of Village Regulation Number 05 of 2020 concerning Village Revenues and Expenditures (APBDes) in 2020: Study in Tanjung Seluai Village, South Seluma District, Seluma Regency - Yudistio Dwi Putra; Mulyadi Mulyadi; Heru Purnawan; Parwito Parwito; Hernowo Novi Yanto; Henny Aprianty; Rahiman Dani (GAYAKU PUBLISHER, 2022)
The purpose of this study was to identify and describe the implementation of Village Regulation Number 05 of 2020 concerning APBDes 2020. This study used a qualitative method. Collecting data in the form of observation, interviews and documentation. Informants in this study amounted to 4 people who meet the criteria of informants. Sample selection using purposive sampling. Based on the results of research on the Implementation of Village Regulation No. 05 of 2020 concerning the 2020 Village Revenue and Expenditure Budget in Tanjung Seluai Village, South Seluma District, Seluma Regency, it can be concluded that: 1. Communication has shown optimal results based on the research conducted has been optimal in terms of transmission , clarity, and consistency when conveying information to policy implementers. 2. Resources also show optimal results where aspects of staff, information, authority are categorized as maximum, but for the aspect of facilities it is not maximized because there are still many facilities that are needed or updated. 3. The disposition shows that the results are less than optimal, it can be seen that the lack of facilities that support the implementation of the program. but the implementers have a high commitment to realizing the village regulations. 4. The bureaucratic structure is categorized as optimal based on research conducted with several informants saying that it is optimal in terms of work guidelines based on SOPs that are easily understood by policy implementers and carry out well. Suggestions for the Village Government to conduct an evaluation through the Camat, especially regarding the accountability for the implementation of the APBDes in Tanjung Seluai Village, where the accountability report has not been carried out properly.